Diversity, equity, and affirmative actions for black brazilians in higher education - Iensue, Geziela (2021)
The recognition of “difference” to promote the existence of an inclusive cultural diversity is not enough to combat the stereotypes and stigmas that still affect blacks in our society. Being “different” in markedly unequal contexts means something that transcends the subject's “brand” refers to the brand that constitutes him socially and establishes himself as a mode of exclusion. This article seeks to problematize the diversity argument as a legitimate foundation to support the policy of racial quotas for access to higher education, in the light of the American and Brazilian pro-diversity jurisprudence. Finally, he argues that the diversity argument combined with the recognition of difference (equity) is adequate to legitimize the policy of reserving places for blacks to enter public higher education in Brazil. The adopted methodology is characterized by a qualitative approach, by the method of critical-dialectic approach and by the methods of bibliographic and documentary procedure.